Direito em fluxo: manifesto das bases globais da valorização do trabalho na ordem econômica - Tuma, Eduardo (2015)
The aim of this thesis to discuss the changes and flows by passing the Law of the globalized society. Economic hegemony and its implications for changes in the science of law will be addressed, especially in the approach that can be observed between the two main Western legal systems: civil law system and the common law system. The comparison extends to a specific analysis of labor relations in countries with different economic conformations